Peletização de sementes de feijão (Phaseolus vulgaris L.) com carbonato de cálcio, rizóbio e molibdênio - BERGER, PAULO GERALDO; VIEIRA, CLIBAS; ARAÚJO, GERALDO A. DE ANDRADE; CASSINI, SÉRVIO TÚLIO ALVES (Revista Ceres, 2015)
.